2020
DOI: 10.1039/d0cy00211a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of heterostructure based on hierarchical Bi2MoO6 and g-C3N4 with ease for impressive performance in photoelectrocatalytic water splitting and supercapacitor

Abstract: This work demonstrates the formation of g-C3N4/Bi2MoO6 heterostructure for water splitting and supercapacitor; which shows highest PEC efficiency and symmetric device delivered a energy density and power density of 47 W h kg−1 and 4.5 kW kg−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 82 publications
0
33
0
Order By: Relevance
“…Several carbon-based materials such as graphene oxide (GO), carbon nanofibers (CNFs), carbon nanotubes (CNTs), ordered mesoporous carbon (OMC), and graphitic carbon nitride (GCN) have been used for electrochemical sensors. Among them, GCN received a lot of attention due to its unique structural characteristics, large surface area, high electrical conductivity, high mechanical strength, and chemical stability. In addition, many researchers have reported that heteroatom (S, N, P) doping in the GCN framework is an excellent strategy for improving its activity more effectively for various electrochemical applications, including sensing, photocatalytic degradation, and water catalysis. Through this, MoN’s stability and electrical conductivity can be enhanced by forming a composite material with heteroatom-doped GCN. As a result, the combination of MoN and heteroatom-doped GCN is expected to significantly enhance the activity of the electrochemical sensor.…”
Section: Introductionmentioning
confidence: 99%
“…Several carbon-based materials such as graphene oxide (GO), carbon nanofibers (CNFs), carbon nanotubes (CNTs), ordered mesoporous carbon (OMC), and graphitic carbon nitride (GCN) have been used for electrochemical sensors. Among them, GCN received a lot of attention due to its unique structural characteristics, large surface area, high electrical conductivity, high mechanical strength, and chemical stability. In addition, many researchers have reported that heteroatom (S, N, P) doping in the GCN framework is an excellent strategy for improving its activity more effectively for various electrochemical applications, including sensing, photocatalytic degradation, and water catalysis. Through this, MoN’s stability and electrical conductivity can be enhanced by forming a composite material with heteroatom-doped GCN. As a result, the combination of MoN and heteroatom-doped GCN is expected to significantly enhance the activity of the electrochemical sensor.…”
Section: Introductionmentioning
confidence: 99%
“…On the other side, two oxidation peaks were obtained at −0.42 and −0.23 V (vs Hg/HgO), which are assigned to the oxidation of Bi 0 → Bi + and Bi + → Bi 3+ , respectively. 26 Also, the CV profile of bare gCN is shown in Figure S1, which is exhibited an ideal symmetric rectangular shape due to the contribution of the EDLC (capacitive) nature of gCN nanosheets. For all of the gCN/BVO nanocomposite materials, the area of the CV profile increases while increasing the gCN content.…”
Section: Resultsmentioning
confidence: 99%
“…This combined system, often called as "supercapattery", may be an asymmetric cell with capacitive and battery electrode 16−20 or composite electrodes that show both capacitive and battery behaviors. 21−25 Recently, bimetal oxides of transition metals such as NiMoO 4 , 19 ZnCo 2 O 4 , 22 Bi 2 MoO 6 , 26 NiCo 2 S 4 , 12 etc. have received significant attention in battery-type electrode materials due to their superior electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Different from other N/C materials, g-C 3 N 4 typically contain complex nitrogen species to provide uniform and abundant nitrogen ligands, providing more metal coordination sites for catalysts, and may also be used as reactive sites for photoelectrocatalysis. [15] In addition, with an optical bandgap of 2.70 eV, g-C 3 N 4 responds to visible light up to 460 nm, which can broaden the absorption range of TiO 2 based device. Nevertheless, as same as pristine TiO 2 , pure g-C 3 N 4 is limited largely due to the low quantum efficiency, and high electron hole recombination rate.…”
Section: Introductionmentioning
confidence: 99%